The Yoruba A New History. - Ogundiran, Akinwumi (Book collections on Project MUSE., 2020)
In The Yoruba: A New History, Akinwumi Ogundiran examines the development of the ideas and practices that have shaped the Yoruba identity and experience going back as far as AD 800.